Functions of synapsins in corticothalamic facilitation: important roles of synapsin I - Nikolaev, Maxim (J Physiol, 2015)
KEY POINTS: The synaptic vesicle associated proteins synapsin I and synapsin II have important functions in synaptic short‐term plasticity. We investigated their functions in cortical facilitatory feedback to neurons in dorsal lateral geniculate nucleus (dLGN), feedback that has important functions in state‐dependent regulation of thalamic transmission of visual input to cortex. We compared results from normal wild‐type (WT) mice and synapsin knockout (KO) mice in several types of synaptic plasticity, and found clear differences between the responses of neurons in the synapsin I KO and the WT, but no significant differences between the synapsin II KO and the WT. These results are in contrast to the important role of synapsin II previously demonstrated in similar types of synaptic plasticity in other brain regions, indicating that the synapsins can have different roles in similar types of STP in different parts of the brain. ABSTRACT: The synaptic vesicle associated proteins synapsin I (SynI) and synapsin II (SynII) have important functions in several types of synaptic short‐term plasticity in the brain, but their separate functions in different types of synapses are not well known. We investigated possible distinct functions of the two synapsins in synaptic short‐term plasticity at corticothalamic synapses on relay neurons in the dorsal lateral geniculate nucleus. These synapses provide excitatory feedback from visual cortex to the relay cells, feedback that can facilitate transmission of signals from retina to cortex. We compared results from normal wild‐type (WT), SynI knockout (KO) and SynII KO mice, in three types of synaptic plasticity mainly linked to presynaptic mechanism. In SynI KO mice, paired‐pulse stimulation elicited increased facilitation at short interpulse intervals compared to the WT. Pulse‐train stimulation elicited weaker facilitation than in the WT, and also post‐tetanic potentiation was weaker in SynI KO than in the WT. Between SynII KO and the WT we found no significant differences. Thus, SynI has important functions in these types of synaptic plasticity at corticothalamic synapses. Interestingly, our data are in contrast to the important role of SynII previously shown for sustained synaptic transmission during intense stimulation in excitatory synapses in other parts of the brain, and our results suggest that SynI and SynII may have different roles in similar types of STP in different parts of the brain.